Photocatalytic removal of gaseous ethanol, acetaldehyde and acetic acid: from a fundamental approach to real cases. (17th November 2022) - Pargoletti, Eleonora; Rimoldi, Luca; Meroni, Daniela; Cappelletti, Giuseppe
ABSTRACT: The photocatalytic oxidation of volatile organic compounds (VOCs) has been extensively investigated. With respect to water treatment, photocatalytic degradation of air pollutants is still less understood, but this has not prevented photocatalytic building materials and air purifiers to reach the market. Here, we provide a selective overview of the current understanding on VOC photocatalytic oxidation, focusing on ethanol, acetaldehyde, and acetic acid. Among the main indoor pollutants, these molecules are also oxidation intermediates of numerous VOCs. Their adsorption at the photocatalyst surface is first presented, based on theoretical and experimental evidence. Reaction intermediates are discussed, comparing proposed reaction mechanisms. The role of the photocatalyst features in directing adsorption and oxidation phenomena is highlighted, encompassing both TiO2 and emerging photocatalysts. We then critically discuss gaps in our knowledge, such as the effect of air humidity, multi-pollutant interactions and deactivation pathways. Finally, attempts to model VOC degradation in realistic conditions are reviewed.